1983
DOI: 10.1128/aem.45.5.1566-1574.1983
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Peptides by Bacteroides ruminicola B 1 4

Abstract: The maximum growth rate of Bacteroides ruminicola B14 was significantly improved when either Trypticase or acetate and C4-C5 fatty acids were added to defined medium containing macrominerals, microminerals, vitamins, hemin, cysteine hydrochloride, and glucose. The organism was unable to grow with peptides as the sole energy source, but growth yields from glucose were significantly improved when Trypticase was added to batch cultures containing basal medium, acetate, and C4-C5 volatile fatty acids. During perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 45 publications
1
30
0
2
Order By: Relevance
“…This difference may again reflect enhanced deamination in the mixed species' incubations as a means of generating energy when energy-yielding substrates were depleted. This supposition agrees with the findings that the availability of fermentable carbohydrates is an important factor in the utilization of peptides and amino acids by rumen bacteria (Maeng et al 1976;Russell 1983;Russell et al 1983).…”
Section: Comparisons Of Mixed and Slngle Cultures Of Rumen Bacterlasupporting
confidence: 92%
See 2 more Smart Citations
“…This difference may again reflect enhanced deamination in the mixed species' incubations as a means of generating energy when energy-yielding substrates were depleted. This supposition agrees with the findings that the availability of fermentable carbohydrates is an important factor in the utilization of peptides and amino acids by rumen bacteria (Maeng et al 1976;Russell 1983;Russell et al 1983).…”
Section: Comparisons Of Mixed and Slngle Cultures Of Rumen Bacterlasupporting
confidence: 92%
“…Most in vitro studies of peptide and amino acid utilization by rumen bacteria have been conducted with mixed populations (Wallace and Cotta 1988;Broderick et al 1991 ;Russell et al 1991). Some classical studies with single species of bacteria and peptide substrates were published during the 1960s (Pittman and Bryant 1964;Pittman et al 1967), but virtually nothing further was reported until the 1980s, as exemplified by the work of Russell (1983). Even I988), and in particular, Preuotella (formerly Bacteroides) rurninicola (Pittman and Bryant 1964;Pittman et al 1967;Munn et al 1983;Russell 1983;McKain et al 1992;Newbold et al 1992;Wallace et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide breakdown in the rumen is part of a degradation process whereby dietary protein is broken down to ammonia, leading to the inefficient utilisation of dietary amino acids [1,2]. The genus Prevotella plays a significant role in this process [2][3][4][5][6][7][8]. The peptidases of Prevotella albensis M384 have been investigated biochemically [5,9,10], and one, a dipeptidyl peptidase IV (DPP-4), has been cloned and characterised [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bladen et al [8] concluded that P. ruminicola was probably the most important ammonia-producing ruminal bacterium, but even the best strain (B 1 4) produced ammonia at a relatively slow rate. When carbohydrates were available, virtually all of the amino nitrogen was incorporated into microbial protein and the deamination rate was even slower [32]. Carbohydrate-fermenting ruminal bacteria did not have deamination rates that could explain the ability of MRB to produce ammonia ; however, HAB have been shown to generate ammonia 20-fold faster [33,34].…”
Section: Discussionmentioning
confidence: 95%